Leucaena leucocephala Trials in Uttar Pradesh - Chaturvedi, A. N. (Indian Forester, 1981)
Trials of high yielding Leucaena varieties imported from Hawaii and Australia etc. are being carried out in Uttar Pradesh since 1976-77. Two varieties of K-8 of Hawaiian and Fiji origins respectively were tried in hills. The Fiji variety exhibited poor growth but the Hawaiian vareity has grown vigorously. The plants grow well only in deep moist soils, and on dry soils manuring and irrigation for two years is required. It can grow upto 13OOm elevation and is vulnerable to heavy damage by cattle, deer, monkeys, etc, The species grows Well even in Lantana infested areas and started producing seeds within six months of planting. Trials of Leucaena varieties in Tarai region showed gummosis during March 1980. The affected tree stops growing, starts drying from the top and generally dies. The species is not considered suitable for plantiog in Tarai region under unirrigated conditions. It has, however, done very well in Clutterbuckganj Nursery at Bareilly in good soil and under irrigated condition. In acidic soils its growth has been observed to be poor but it has done very well on soil with pH of about 9.00. It can tolerate light shade but is not suitable for frosty areas or those with clayey soils. Pre-treatment with scarification, boiling in water, soaking in water for 24-48 hours has given about 85% germination. However, Leucaena has also been observed to germinate freely from seed even without treatment and the ground floor in old plantations is carpeted with seedlings.